Simultaneous vibration suppression and energy harvesting: Damping optimization for performance limit. (1st October 2019) - Wang, Jiqiang
Highlights: Optimal design for simultaneous vibration suppression and energy harvesting is dealt with through a geometric approach. Limit of performance is obtained which would otherwise be difficult to deal with. Relationship between performance specifications is clarified revealing non-necessity of design compromise. Both fundamental vs non-fundamental constraints are considered. Important concept of ineffective designs is explored. Abstract: Non-conventional vibration absorbers have been promising due to their capability of transforming dissipated energy for harvesting purpose. These optimized tuned mass damper/harvester devices thus pose a challenging problem of optimal design for simultaneous vibration suppression and energy harvesting. This problem has been conventionally tackled through optimization methods where feasible parameters are designed through extensive search over the designated functional spaces. In this paper, however, a geometric approach is proposed to handle this simultaneous design problem. A variety of important issues such as performance limit, design compromise, fundamental and non-fundamental constraints handling, as well as ineffective designs are considered through geometric representations. Useful design guidelines are revealed that would otherwise be lost during optimization process. Numerical examples are provided to illustrate both the theoretical results and design guidelines.